B. adolescentis ameliorates chronic colitis by regulating Treg/Th2 response and gut microbiota remodeling. (1st January 2021) - Fan, Lina; Qi, Yadong; Qu, Siwen; Chen, Xueqin; Li, Aiqing; Hendi, Maher; Xu, Chaochao; Wang, Lan; Hou, Tongyao; Si, Jianmin; Chen, Shujie
ABSTRACT: Inflammatory bowel disease (IBD) is defined as an immune dysregulation disease with poor prognosis. Various therapies based on gut microbe modulation have been proposed. In this study, we aim to explore the therapeutic effect of B. adolescentis on IBD, as well as the immune and microecology mechanism of B. adolescentis in IBD. The fecal level of B. adolescentis was decreased in the IBD patients compared with the normal people in our cohort and the GMrepo database. To further clarify the role of B. adolescentis in IBD, we induced chronic colitis with three cycles of dextran sulfate sodium (DSS). We found B. adolescentis gavage exhibited protective effects as evidenced by the significantly decreased diarrhea score, spleen weight, and increased colon length. Accordingly, the cumulative histological grading was decreased in the B. adolescentis administration group. In addition, tight junction protein and mucin family were enhanced after B. adolescentis treatment. Furthermore, distinct effects were found with decreased pro-inflammatory cytokines such as TNF-α, IL-6, IL-1β, IL-18, IL-22, IL-9 and increased anti-inflammatory cytokines IL-10, IL-4, IL-5. Importantly, the colon lamina propria in the B. adolescentis group consisted of more Treg and Th2 cells, which inhibited extreme gut inflammation. Additionally, 16srRNA sequencing showed an evident increase in the B:F ratio in the B. adolescentis group. In particular, B. adolescentis application inhibited the excessive growth of Akkermansia and Escherichia-Shigella in genus level. In conclusion, B. adolescentis refined the DSS-induced chronic colitis by stimulating protective Treg/Th2 response and gut microbiota remodeling. B. adolescentis regularly treatment might improve the therapeutic effects for inflammatory bowel disease.